Marketing Strategy for Overlay Perfume Products on TikTok and Instagram in Creating Brand Awareness - Andika Suryo Ramadhan; Yovi Bathesta (Majapahit Journal of Islamic Finance and Management, 2026)
The development of social media has changed the pattern of marketing communication, particularly in the perfume industry which relies heavily on visual, emotional, and brand identity aspects. TikTok and Instagram are the two main platforms that businesses use to build brand awareness effectively, especially among the younger generation. This study aims to analyze the marketing strategy of Perfume Overlay products through TikTok and Instagram in creating brand awareness at the level of brand recognition. This study uses a qualitative descriptive approach with a project planning method, and adopts the AISAS (Attention, Interest, Search, Action, Share) model, SOSTAC (Situation, Objectives, Strategy, Tactics, Action, Control) framework. The object of the research is the local perfume brand Parfum Overlay with a focus on digital marketing activities on the brand's official TikTok and Instagram accounts. Data was collected through observation of social media content, engagement analysis, and evaluation of visual communication strategies and audience interaction. The results of the study show that the combination of creative video content, visual storytelling, brand identity consistency, and the use of interactive features such as reels, short videos, and user-generated content can significantly increase the brand recognition of Parfum Overlay. TikTok plays a big role in creating awareness quickly through viral content, while Instagram functions to strengthen brand image through aesthetic and consistent visual display. This study concludes that integrated marketing strategies through TikTok and Instagram are effective in building brand awareness of Perfume Overlay, especially at the brand recognition level. These findings are expected to make practical contributions to local business people in designing relevant digital marketing strategies as well as academic contributions to the study of digital marketing communication in the perfume industry.